2007
DOI: 10.1007/s11547-007-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of chest radiography in the diagnosis of allergic bronchopulmonary aspergillosis in adult patients with cystic fibrosis

Abstract: Our results demonstrate the limited usefulness of chest radiography in the diagnosis of ABPA in patients with cystic fibrosis. The most significant abnormalities are nonspecific and commonly seen on baseline films in cystic fibrosis without ABPA and persist after treatment in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Cortese et al [25] confirmed the relative insensitivity of plain chest radiography as applied to diagnosing ABPA. Cortese et al [25] confirmed the relative insensitivity of plain chest radiography as applied to diagnosing ABPA.…”
Section: Chest Ct Imaging and Recognition Of Abpamentioning
confidence: 94%
“…Cortese et al [25] confirmed the relative insensitivity of plain chest radiography as applied to diagnosing ABPA. Cortese et al [25] confirmed the relative insensitivity of plain chest radiography as applied to diagnosing ABPA.…”
Section: Chest Ct Imaging and Recognition Of Abpamentioning
confidence: 94%
“…Expiratory CT identifies SAD and ideally should be controlled by spirometry [98,99] . SAD is recognised by the presence of hypodense areas within areas of mosaic attenuation and it is estimated that one third of hypodense regions persist over a 2 year period, which suggests irreversibility [12] . This may be used as a separate marker of pulmonary disease in conjunction with CT bronchiectasis scores.…”
Section: Dose Optimisation Protocolsmentioning
confidence: 99%
“…Cortese et al [ 25 ] confi rmed the relative insensitivity of plain chest radiography as applied to diagnosing ABPA. In contrast, chest CT readily shows typical central (inner third of bronchial tree) segmental and subsegmental varicose or cystic bronchiectasis, mucoid impaction, and centrilobular nodules in small airways (ie, certain CT changes are sensitive but not specifi c for ABPA) [ 26 , 27 ].…”
Section: Chest Ct Imaging and Recognition Of Abpamentioning
confidence: 99%